Worker knowledge sharing in logistics services: case of a Brazilian aircraft manufacturer - Ferreira Filho, Angelo José Castro Alves; Junior, Jorge Muniz; Cunha, Julio Cicero (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose - This paper assesses factors that enable tacit knowledge sharing among logistic workers at Brazilian aircraft manufacturer. Design/methodology/approach - The proposal methodology is supported by a mixed methods approach to examine how organizations can develop favorable contexts to explore knowledge sharing relations among workers in the Logistics area of a Brazilian aircraft manufacturer. The proposal has a qualitative phase based on local interviews, informal conversations and on-site observations. The quantitative phase entails a ranking of the different factors that support knowledge sharing in terms of their relative importance to each other, using the Analytic Hierarchy Process with Incomplete Pairwise Comparison (AHP-IPC). Findings - Our overall results indicated that Understanding of Work Instruction and Registration in Work Instruction were perceived as the most important processes among the logistic workers, followed by Conversation among Workers. Based on the qualitative phase analysis it was possible to observe that the factors Incentive, Work Instruction, Zero Defect and Training were considered relevant. Research limitations/implications - This study was limited to the logistics department of a Brazilian aircraft manufacturer and its logistic workers. Practical implications - The findings contribute to support managers to deal knowledge sharing through efficient communication, collaboration and thrust among workers in the company. Originality/value - This is the first study in a Logistics department of a Brazilian aircraft manufacturer applying the proposal methodology based on questionnaires in order to capture the workers perception of the resilience and knowledge sharing in the shop floor and it is very relevant due the complexity of the operation in a logistic area of an aircraft manufacturer. Keywords: Knowledge Sharing, Logistic, Aircraft Manufacturer, Brazil.